Thermophysical properties and C02 solubility in ionic liquids. N-Methyldiethanolamine and their binary mixtures - MAJEED AKBAR, MAJID (2013)
Incorporating the advantage of both ILs and amines for the development of hybrid solvent to capture C02 is drawing great attention. Therefore in the present work a fundamental and systematic investigation on the potential application of hybrid mixtures (comprising of ILs + amine) for C02 removal has been presented. The binary mixtures of three imidazolium based ILs namely; 1-hexyl-3- methylimidazolium tetrafluoroborate ([hmim][BF 4]). 1-hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([hmim] [Tf2N]). 1-hexy 1-3-methy limidazolium tris(pentafluoroethyl)trifluorophosphate ([hmim] [F AP]) with N-methyldiethanolamine (MDEA) were prepared and the C02 solubility was measured in the pure solvents as well as in the binary mixtures at three different temperatures (298.15, 313.15, 323.15) K and at eight different pressures (:S 3000 kPa). Prior to C02 solubility the basic thermophysical properties namely; density (p), viscosity (1)), refractive index (no) and thermal stability (TGA) of the pure solvents as well as for the binary mixtures were measured over a wide range of temperatures (298.15 to 323.15 for p, 1), no and 303.15 to I 073.15 for TGA) and concentrations (for binary mixtures). The excess properties for the binary mixtures namely; excess molar volumes, viscosity and refractive index deviation were deduced from the measured physical properties data. The effects of pressures. temperatures, concentrations, and anions on C02 solubility were studied in detail. The temperature depended parameters of solubility namely; Henry's constants, Enthalpy, Entropy were also deduced. The experimental C02 solubility results were modelled with the help of Peng-Robinson and Soave-Redlich Kwong equations of states (EOS) with Vander Waals (VdW) and Mathias-Klotz-Prausnitz (MK) mixing rules. The pure liquids and the selected binary mixtures which were once used for C02 solubility were regenerated and used again to investigate their potential applicability for recycling purpose.